Effect of arc current on mechanical properties of AlCrN coatings deposited using cathodic arc evaporation - Warcholinski, B.; Gilewicz, A.; Kuprin, A.S. (Вопросы атомной науки и техники, 2022)
The AlCrN coatings were formed using cathodic arc evaporation at constant nitrogen pressure and arc current ranged from 50 to 120 A. Scanning electron microscopy, energy dispersive analysis, X-ray diffractometry, nanoindentation, adhesion tests and friction tests were used to investigate the effect of arc current on surface morphology, composition, structure, and mechanical and tribological properties of coatings. It was found that all coatings present cubic AlCrN with Al/(Al+Cr) ratio independent on arc current. Increase in the arc current results in increase in lattice parameter, crystallite size as well as deposition rate and coating surface roughness. A decrease in hardness with a simultaneous increase in Young's modulus is also observed. The adhesion of the coatings shows a non-linear character with the maximum (108 N) for the coating formed at an arc current of 80 A, which may explain the best wear resistance – the lowest wear rate 1.4·10⁻⁷ mm³/Nm. Покриття AlCrN були осаджені за допомогою катодного дугового випаровування при постійному тиску азоту та струмі дуги в діапазоні від 50 до 120 A. Використовували скануючу електронну мікроскопію, енергодисперсійний аналіз, рентгенівську дифрактометрію, наноіндентування, тести на адгезію та на тертя для дослідження ефекту впливу струму дуги на морфологію поверхні, склад, структуру, механічні та трибологічні властивості покриттів. Було виявлено, що всі покриття містять кубічний AlCrN із співвідношенням Al/(Al+Cr), не залежним від струму дуги. Збільшення струму дуги призводить до збільшення параметра решітки, розміру кристалітів, а також швидкості осадження та шорсткості поверхні покриття. Також спостерігається зниження твердості з одночасним збільшенням модуля Юнга. Адгезія покриттів має нелінійний характер з максимумом (108 Н) для покриття, сформованого при струмі дуги 80 А, що може пояснити найкращу зносостійкість – найменша швидкість зношування 1.4·10⁻⁷ mm³/Нм.